High risk and probability of progression to osteoporosis at 10 years in HIV-infected individuals: the role of PIs. (1st June 2018) - Negredo, Eugènia; Langohr, Klaus; Bonjoch, Anna; Pérez-Alvárez, Núria; Estany, Carla; Puig, Jordi; Rosales, Joaquim; Echeverría, Patricia; Clotet, Bonaventura; Gómez, Guadalupe
Abstract: Background: Osteoporotic fractures still remain very infrequent and physicians rarely evaluate bone health. We wanted to assess the magnitude of this problem in the near future by determining the risk and likelihood of progression to osteoporosis. Methods: We estimated the risk of progression to osteopenia/osteoporosis among HIV-infected patients with at least 2 DXA scans (3726 scans from 875 patients). Time-non-homogeneous bidirectional multistate models based on three states (normal bone mineral density, osteopenia and osteoporosis) were used to model the progression of bone mineral density as a function of age and to study the association between the risk of bone loss and antiretroviral use. Results: The HRs associated with age (>45 versus ≤45 years) were: (i) from normal bone mineral density to osteopenia, 0.71 (95% CI 0.45–1.11) for men and 1.06 (95% CI 0.55–2.05) for women; and (ii) from osteopenia to osteoporosis, 0.83 (95% CI 0.51–1.35) for men and 0.99 (95% CI 0.38–2.56) for women. The transition probabilities from osteopenia to osteoporosis over 10 years among men aged 30 and 50 years were 14.9% (95% CI 10.5%–20.4%) and 19% (95% CI 14.3%–24.3%), respectively; and for women, 6.9% (95% CI 3.1%–14.4%) and 30.1% (95% CI 19.8%–41.8%), respectively. An increased osteoporosis risk was observed for PIs and PIs + tenofovir disoproxil fumarate; darunavir was associated with a higher risk of osteoporosis among men (HR 3.9; 95% CI 2–7.5) and women (HR 4.5; 95% CI 1.4–14.7); and atazanavir was associated with a higher risk of osteoporosis among women (HR 4.2; 95% CI 1.3–14). Conclusions: Our results highlight the importance of monitoring bone mineral density given the high probability of progression to osteopenia/osteoporosis, especially in women. In the future, changes in antiretrovirals other than tenofovir, such as PIs, should be recommended to reduce the risk of fracture.